Bacterial oxygen production in the dark - Ettwig, Katharina F.; Speth, Daan R.; Reimann, Joachim; Wu, Ming L.; Jetten, Mike S.M.; Keltjens, Jan T. (Frontiers in Microbiology, 2012)
Nitric oxide (NO) and nitrous oxide (N2O) are among Nature’s most powerful electron acceptors. In recent years it became clear that microorganisms can take advantage of the oxidizing power of these compounds to degrade recalcitrant aliphatic and aromatic hydrocarbons. For two unrelated bacterial species, the ‘NC10’ phylum bacterium ‘Candidatus Methylomirabilis oxyfera’ and the γ-proteobacterial strain HdN1 it has been suggested that under anoxic conditions with nitrate and/or nitrite, monooxygenases are used for methane and hexadecane oxidation, respectively. No degradation was observed with nitrous oxide only. Similarly, “aerobic” pathways for hydrocarbon degradation are employed by (per)chlorate-reducing bacteria, which are known to produce oxygen from chlorite (ClO2-). In the anaerobic methanotroph M. oxyfera, which lacks identifiable enzymes for nitrogen formation, substrate activation in the presence of nitrite was directly associated with both oxygen and nitrogen formation. These findings strongly argue for the role of NO, or an oxygen species derived from it, in the activation reaction of methane. Although oxygen generation elegantly explains the utilization of ‘aerobic’ pathways under anoxic conditions, the underlying mechanism is still elusive. In this perspective we review the current knowledge about intra-aerobic pathways, their potential presence in other organisms and identify candidate enzymes related to quinol-dependent NO reductases (qNORs) that might be involved in the formation of oxygen.